Stymied by a wealth of health information: how viewing conflicting information online diminishes cancer screening. (2nd January 2019) - Marshall, Laura H.; Comello, Maria Leonora
ABSTRACT: Background: Confusing information about cancer screening proliferates even within credible sources online, particularly around mammography and prostate antigen testing. One story may emphasize the benefits of screening while another focuses on its risks. How does this contradiction affect readers of these stories? Method: Survey participants were recruited online via social media. Across two experiments, one focusing on breast cancer risk perception and the other on prostate cancer, we randomized participants into four groups to see social media posts that contained conflicting information with or without the element of potential harm. The control group saw messages supporting preventive screening tests without conflict between posts. Results: In both experiments, conflict was shown to reduce both self-efficacy and response efficacy. Men and women responded differently to messages that included the potential of harm from screening tests. Conclusions: We found support for the notion that exposure to conflicting information decreases self-efficacy and response efficacy, potentially discouraging the likelihood of behavior change that could prevent cancer. The additional finding that women's self-efficacy was reduced by uncertainty but not by the potential for harm – while men's self-efficacy was conversely reduced by harm potential but not uncertainty – may be an important consideration in communication efforts to encourage screening.